Effects of couples positive massage programme on wellbeing, perceived stress and coping, and relation satisfaction. Issue 1 (1st January 2019) - Naruse, Sayuri M.; Moss, Mark
ABSTRACT: Objectives: Although supporting preventative self-regulation and self-care activity for daily stress is important as dyadic coping, there seems a paucity of exploration of non-verbal interventions such as tactile communication. This preliminary experimental study assessed the efficacy of a short educational massage programme for healthy but stressed couples. The study aimed to investigate if the educational mutual massage (Positive Massage) programme has any acute and sustained effects on wellbeing, perceived stress and coping, and relationship satisfaction among couples. Design: A pseudo randomised two group design employing a delayed treatment element assessed the effects of the Positive Massage programme and subsequent at-home application. Thirty-eight participants completed a three-week massage course. Main Outcome Measures: Measurements of the Warwick-Edinburgh Mental Well-being Scale, the Rhode Island Stress and Coping Inventory, and the Positive Feelings Questionnaire were collected online using Qualtrics at three time points (the start, the end, and three weeks after the course). Data were analysed with mixed ANOVAs. Results: Mental wellbeing, and perceived stress and coping significantly improved from before to after the Positive Massage programme. There was no significant decline after the cessation of the massage programme. Relationship satisfaction did not show significant changes from the initial assessment. Conclusions: The overall effects of the Positive Massage programme indicate the importance of developing further large scale studies of mutual massage as a safe and beneficial self-care activity. This innovative study has laid the groundwork for future studies into the possibility of mutual massage as a self-regulation dyadic coping strategy for home use to improve overall wellbeing.